A True Triaxial Stress Cell to Simulate Deep Downhole Drilling Conditions - Rasouli, Vamegh; Evans, Brian (Australian Petroleum Production and Exploration Association, 2010)
Conventional rock mechanics experiments using triaxial cells trying to simulate the true downhole stress field by applying equal horizontal stresses, fundamentally fail to treat real field borehole conditions as three independent stresses. In the real world, the horizontal stress field at shallow depth can have a different direction from that at greater depths, resulting in well failure if the driller is not careful. Core samples used in small cells applying uniaxial stress simply cannot be used to properly simulate these anomalous downhole stress fields. A True Triaxial Stress Cell (TTSC) has been built to overcome this problem by properly simulating the true earth stresses. This technology will mimic stresses in deep oil and gas fields existing in highly anisotropically stressed environments. The TTSC allows vertical and two independent horizontal stresses to be applied up to 50 MPa in each direction on a 30 cm cube of rock and, at the same time, allows pore pressure to be applied up to 21 MPa. Through a hole drilled through the centre of the rock, a fluid can be injected to simulate hydraulic fracturing, or CO2 injection into saline aquifers or coal. Sanding analysis can be performed by increasing pore pressure and producing pore fluid from the borehole. Formations having different geological properties may be simulated, while deviated drilling through the rock simulates the deviated stresses when drilling horizontal wells. Fracture propagation, sanding initiation, and in-flow production performance is monitored in real-time using ultrasonic seismic transducers mounted around the sample.